Safety and Feasibility of Same Day Discharge Strategy for Primary Percutaneous Coronary Intervention - Jehangir Ali Shah; Tahir Saghir; Bashir Ahmed; Syed Alishan ul Haq; Rajesh Kumar; Muhammad Naeem Mengal; Mehwish Zehra; Syeda Sakeena Raza; Musa Karim; Nadeem Qamar (Ubiquity Press, 2021)
Background: The strategy for early discharge after primary percutaneous coronary intervention (PCI) could have substantial financial benefits, especially in low-middle income countries. However, there is a lack of local evidence on feasibility and safety of the strategy for early discharge. Therefore, the aim of this study was to assess the safety of early discharge after primary PCI in selected low-risk patients in the population of Karachi, Pakistan. Methods: In this study 600 consecutive low-risk patients who were discharged within 48 hours of primary PCI were put under observation for major adverse cardiac events (MACE) after 7 and 30 days of discharge respectively. Patients were further stratified into discharge groups of very early (≤ 24 hours) and early (24 to 48 hours). Results: The sample consisted of 81.8% (491) male patients with mean age of 54.89 ± 11.08 years. Killip class was I in 90% (540) of the patients. The majority of patients (84%) were discharged within 24 hours of the procedure. Loss to follow-up after rate at 7 and 30 days was 4% (24) and 4.3% (26) respectively. Cumulative MACE rate after 7 and 30 days was observed in 3.5% and 4.9%, all-cause mortality in 1.4% and 2.3%, cerebrovascular events in 0.9% and 1.4%, unplanned revascularization in 0.9% and 1.2%, re-infarction in 0.3% and 0.5%, unplanned re-hospitalization in 0.5% and 0.5%, and bleeding events in 0.5% and 0.5% of the patients respectively. Conclusion: It was observed that very early (≤ 24 hours) discharge after primary PCI for low-risk patients is a safe strategy subjected to careful pre-discharge risk assessment with minimal rate of MACE after 7-days as well as 30-days.